1975
DOI: 10.1182/blood.v45.3.395.395
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia: confirmation of diagnosis with in vitro methods

Abstract: Profound thrombocytopenia developed in a patient during treatment with heparin for venous thrombosis. The platelet count increased toward normal when heparin administration was stopped, but fell abruptly when the drug was again given. Platelet aggregation occurred when heparin was added to the patient's platelet-rich plasma, or to normal platelets plus the patient's serum. This serum also effected release of 3H- serotonin from normal platelets. This pattern of aggregation was clearly different from that occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(39 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…Thrombocytopenia and thromboembolism are well recognized complications of heparin therapy [I-61. These complications are considered to be mediated by an idiosyncratic immunological mechanism which renders platelets hypersensitive to heparin [1][2][3][4][5][6]. However, some patients developed consumptive thrombocytopenia following heparin therapy within hours of initiating treatment and without prior exposure to heparin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia and thromboembolism are well recognized complications of heparin therapy [I-61. These complications are considered to be mediated by an idiosyncratic immunological mechanism which renders platelets hypersensitive to heparin [1][2][3][4][5][6]. However, some patients developed consumptive thrombocytopenia following heparin therapy within hours of initiating treatment and without prior exposure to heparin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, this effect is different from the heparindependent aggregating factor noted in these patients. Similarly, some studies have demonstrated enhanced serotonin release from normal platelets incubated with patient sera or plasma [14,. The PF3 immuno-injury test for platelet antibodies has also been positive in some patients [15,171 .…”
Section: Delay Ed Onset H Epar I N-l N Duced Th Rombocytopen I Amentioning
confidence: 92%
“…Laake et a1 [29] PATHOPHYSIOLOGY Enhanced peripheral destruction of platelets is believed to be the mechanism of thrombocytopenia in these cases based upon bone marrow examinations (Table I) and the demonstration of a shortened platelet survival [24], but the reason for this remains unsettled. Many investigators have detected a heparin-dependent platelet aggregating factor (PAF) in the blood of patients with this disorder [14,15,19,, while others have not [30,33]. Heparin has been shown to produce platelet aggregation in vitro, but at very high doses [34] .…”
Section: Delay Ed Onset H Epar I N-l N Duced Th Rombocytopen I Amentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of thrombocytopenia is as high as 30% with beef lung heparin preparations [69] but appears much lower with heparin derived from porcine intestine [70,71]. Considerable in vitro evidence is accumulating for the presence of heparin-dependent antiplatelet antibodies in many of these patients [72][73][74][75][76], but not in all [77]. A separate review of heparin thrombocytopenia will appear soon in this journal.…”
Section: Additional Considerationsmentioning
confidence: 99%